Infective endocarditis of partial atrioventricular septal defect – A case report - Stefanović, Maja; Srdanović, Ilija; Milovančev, Aleksandra; Šušak, Stamenko; Tadić, Snežana; Ilić, Aleksandra (Vojnosanitetski pregled, 2021)
Introduction. Partial atrioventricular septal defect (AVSD) is a form of congenital heart disease (CHD) rarely detected in adults. Infective endocarditis represents a severe complication that carries a substantial risk. Case report. We here reported a case of a 43-year-old female with previously diagnosed adult CHD (partial AVSD and bicuspid aortic valve) presented to the hospital with fever and malaise 14 days prior to admission. On the lung computed tomography scan inflammatory consolidations were found and dual antibiotic therapy (ceftazidime and clarithromycin) was administered without significant regression of pulmonary inflammatory consolidations. The antibiotic treatment was continued with amoxicillin/clavulanic acid combined with levofloxacin and metronidazole. Transthoracic and transesophageal echocardiography revealed a large vegetation (dimension, 3.6 x 1.8 cm) attached to the septal leaflet of the tricuspid valve floating between right atrium and right ventricle through tricuspid valve with high embolic potential. Endocarditis team reached a decision for immediate surgical intervention. The operative findings revealed the partial AVSD, common atrioventricular valve with cleft of the anterior mitral leaflet in the A2 segment and detached and cleft septal leaflet of the tricuspid valve. Vegetation (size 4 x 3 cm) was attached to the septal side of the tricuspid annulus, basal segment of the anterior mitral leaflet and edge of the atrial septal defect freely floating between right atrium, right ventricle and left atrium. Excision of the vegetation and AVSD plastics were done, as well as the reconstruction of the mitral and tricuspid annuli and leaflets. The treatment was continued with antibiotics and completed in 18 days with full recovery. Conclusion. Early and precious diagnosis and optimal management that combines both conventional and surgical approaches are crucial for reducing the risk of complications and mortality in patients with infective endocarditis in grown-up congenital heart disease.